EFFECT OF MARKETING MIX (7P) ON PURCHASING DECISION AT CAFE PALAPA - Nova Novitasari; Sugiharto Pujangkoro; Satia Negara Lubis (Jurnal Cakrawala Ilmiah, 2024)
This research aims to analyze effect of marketing mix (7P) on purchasing decision at Cafe Palapa. The methodology used in this research is a quantitative methodology. The customers who visited Cafe Palapa were the population that the researchers used, which was 5,890 people. The Slovin technique was used to calculate 100 Cafe Palapa samples to obtain fairly representative results with an error rate of 10%. The analytical method used in this research is multiple regression to test the hypothesis partially (t). The research results show that product has a positive and significant effect on purchasing decision at Cafe Palapa. Price has a negative and significant effect on purchasing decision at Cafe Palapa. Place has a positive and significant effect on purchasing decision at Cafe Palapa. Promotion has a positive and significant effect on purchasing decision at Cafe Palapa. People has a positive and significant effect on purchasing decision at Cafe Palapa. Process has a positive and significant effect on purchasing decision at Cafe Palapa. Physical evidence has a positive and significant effect on purchasing decision at Cafe Palapa